Surface Modification of Polycarbonate Using Mesh Electrode at Atmospheric Pressure Discharge at 50 Hz - Shrestha, A.K.; Dotel, B.S.; Dhungana, S.; Shrestha, R.; Baniya, H.B.; Joshi, U.M.; Subedi, D.P, (Kathmandu University Journal of Science Engineering and Technology, 2014)
This paper reports the result of surface treatment of polycarbonate sample on atmospheric pressure dielectric barrier discharge (APDBD) in argon environment. The discharge was generated in parallel plate DBD system with a fine metal mesh below a barrier using a high voltage power supply (0-20KV) operating at line frequency, 50Hz. The main objective of the study is to investigate improvement of the hydrophilic property of the polymer after the treatment in plasma. The plasma treated samples were characterized by gravimetric method and contact angle measurement with two test liquids and the contact angle data were used for the calculation of surface energy of the samples with its polar and dispersive components. Our result showed that the discharge produces significant improvement in hydrophilicity just after 2 minutes of treatment reducing the contact angle from 88.28° to less than 55°. It was also found that the change in surface energy is mainly due to the increase in polar component of the surface energy.